Achieving universal health coverage for people with stroke in South Africa: protocol for a scoping review. Issue 10 (12th October 2020) - van Niekerk, Sjan-Mari; Inglis-Jassiem, Gakeemah; Kamalakannan, Sureshkumar; Fernandes, Silke; Webster, Jayne; English, Rene; Smythe, Tracey; Louw, QA
Abstract : Introduction: Stroke is the second most common cause of death after HIV/AIDS and a significant health burden in South Africa. The extent to which universal health coverage (UHC) is achieved for people with stroke in South Africa is unknown. Therefore, a scoping review to explore the opportunities and challenges within the South African health system to facilitate the achievement of UHC for people with stroke is warranted. Methods and analysis: The scoping review will follow the approach recommended by Levac, Colquhoun and O'Brien, which includes five steps: (1) identifying the research question, (2) identifying relevant studies, (3) selecting the studies, (4) charting the data, and (5) collating, summarising and reporting the results. Health Systems Dynamics Framework and WHO Framework on integrated people-centred health services will be used to map, synthesise and analyse data thematically. Ethics and dissemination: Ethical approval is not required for this scoping review, as it will only include published and publicly available data. The findings of this review will be published in an open-access, peer-reviewed journal and we will develop an accessible summary of the results for website posting and stakeholder meetings.